Content Analysis of the Fourth Grade Mathematics Curriculum in Palestine in Light of Thinking Skills - Othman, Ahmed Mohammed; Jawabreh, Reem Mash‘hour (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to analyze the content of fourth grade’s mathematics curriculum in Palestine in light of lower- and higher-order thinking skills in the areas of numbers and arithmetic operations, geometry, algebra, statistics, and data. The study used a content analysis approach that involved objectively and quantitatively description of the content. The results of the curriculum analysis showed that the level of lower-order thinking, based on knowledge, constitutes 39% of mathematics textbook, while the level of average thinking, based on understanding and application, constitutes 44%. As for the level of higher-order thinking, based on analysis, synthesis, and evaluation, it occupies the least percentage of 17%. The study recommended the inclusion of thinking skills in the mathematics textbook through various educational activities that encourage both higher-order and lower-order thinking skills, such as cooperative games, group discussions, problem-solving, thinking outside the box, innovation, and generating creative ideas. Additionally, the study suggested the development of awareness programs for teachers regarding enriching the mathematics course with questions that promote the use of both lower-order and higher-order thinking skills.